Reversible valproate hepatotoxicity due to mutations in mitochondrial DNA polymerase γ (POLG1) - McFarland, R (BMJ Publishing Group, 2009)
We report the case of a 2-year-old boy with seizures who developed hepatic failure shortly after commencing sodium valproate. Unexpectedly, liver function returned to normal on stopping the drug. Sequencing of the mitochondrial polymerase γ gene (POLG1) revealed four heterozygous substitutions, two of which have been identified in cases of Alpers–Huttenlocher disease.